Students’ Possession of Social and Emotional Learning Competencies in the Second Cycle Schools of Basic Education in the Sultanate of Oman - Ali Said Sulayiam Al Matari; Moza Abdullah Almoqbali; Iman Mohammad Almaawali (Gulf Education and Social Policy Review)
The study aimed to identify the degree of students’ social and emotional learning competencies in the schools of the second episode of basic education in Oman after the COVID-19 pandemic, and the researchers used the descriptive curriculum. The questionnaire of the OECD study was used for social and emotional skills in learning (Kankaraš and Suarez-Alvarez, 2019) which consisted of 5 competencies and 30 indicators: accomplishing tasks; emotional organization; dealing with others; cooperation; and openness. The results of the study showed that the overall degree of students’ ownership of social and emotional learning competencies was largely, with an average account (3.70), 74%, and a degree of ownership of each competency to a large extent, and in proportions percentage, ranged from 60.3% to 82%. There are statistically significant differences in the degree to which students have social and emotional learning competencies in the schools of the second episode of basic education in Oman in the total degree attributable to the sex variable, in favor of females (female students), while there are no statistically significant differences in the degree to which students have the competencies of social and emotional learning in the overall degree depending on the age variable. The study recommended that social and emotional learning skills be integrated into the curriculum, and that the Ministry of Education adopt courses, workshops, and lectures on emotional social learning programs aimed at educating all educational, community and media institutions.